2015
DOI: 10.1097/yco.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

Pet ownership and physical health

Abstract: The value of pet ownership and animal-assisted therapy (AAT), as a nonpharmacological treatment modality, augmentation to traditional treatment, and healthy preventive behavior (in the case of pet ownership), is starting to be realized. However, more investigations that employ randomized controlled trials with larger sample sizes and investigations that more closely examine the underlying mechanism of the pet-health effect, such as oxytocin, are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 72 publications
0
41
0
3
Order By: Relevance
“…We chose saliva because one fundamental aspect of the human-canine bond is the gesture of licking that spreads oral cavity microbes on the recipient's skin surface. Recognizing that L. reuteri ATCC 6475 bacteria collected from human milk was found to up-regulate oxytocin when fed to mouse models [30], and that oxytocin is pivotal in caninehuman bonds and weight control [2, [36][37][38], we postulated that dogs may harbor and spread similar microbes that modulate oxytocin and impart a slim physique in the recipient. To test this possibility, we first interrogated the canine oral microbiome using molecular assays and microbial culture (Figure 1).…”
Section: Canine Oral Bacterial Flora Includes Lactobacillus Sppmentioning
confidence: 99%
“…We chose saliva because one fundamental aspect of the human-canine bond is the gesture of licking that spreads oral cavity microbes on the recipient's skin surface. Recognizing that L. reuteri ATCC 6475 bacteria collected from human milk was found to up-regulate oxytocin when fed to mouse models [30], and that oxytocin is pivotal in caninehuman bonds and weight control [2, [36][37][38], we postulated that dogs may harbor and spread similar microbes that modulate oxytocin and impart a slim physique in the recipient. To test this possibility, we first interrogated the canine oral microbiome using molecular assays and microbial culture (Figure 1).…”
Section: Canine Oral Bacterial Flora Includes Lactobacillus Sppmentioning
confidence: 99%
“…Many positive effects of keeping domestic pets and regular contact with animals have been reported; recent studies have increasingly, though not yet sufficiently, confirmed these reports 16. Effects do vary according to animal species or according to the kind of contact with the animal owner and its frequency, or—in the context of animal-assisted therapy (AAT)—with the patient.…”
Section: Benefits Of and Concerns About Live Animals In Domestic Settmentioning
confidence: 99%
“…Effects do vary according to animal species or according to the kind of contact with the animal owner and its frequency, or—in the context of animal-assisted therapy (AAT)—with the patient. But prima facie, the human–animal relationship benefits especially the elderly, for example those with cognitive disabilities 16 17. It is reported that animals offer their elderly owners changes in daily routines; they are communication partners and in some cases better able to establish a relationship with an individual than other people.…”
Section: Benefits Of and Concerns About Live Animals In Domestic Settmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of this growth has been stimulated by the increasing appreciation of the value of pets to human health and well-being through both physical and emotional effects. Studies indicate associations between pet ownership and(or) animal-assisted therapy and numerous aspects of positive health outcomes, ranging from improved cardiovascular health to enhanced mental well-being [3, 4]. Humans, reciprocally, are engaged in gaining a deeper understanding of nutrient requirements and the effects of diet and care practices on the health, metabolism, and behavior of cats and dogs of all ages, breeds, and lifestyles.…”
mentioning
confidence: 99%